Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26599/tst.2019.9010013
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of the local correlation of learning behaviors to predict dropouts from MOOCs

Abstract: Recently, Massive Open Online Courses (MOOCs) have become a major online learning methodology for millions of people worldwide. However, the dropout rates from several current MOOCs are high. Usually, dropout prediction aims to predict whether a learner will exhibit learning behaviors during several consecutive days in the future. Therefore, the information related to the learning behaviors of a learner in several consecutive days should be considered. After in-depth analysis of the learning behavior patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 11 publications
0
36
0
12
Order By: Relevance
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Instructional design factors are critical to the commitment and completion rates. Skills such as motivation for achievement and self-esteem, self-efficacy, effectiveness, design, and development are crucial elements to consider in the instructional design [17] and, since they are new learning models, studies should be conducted to learn in detail about the changes that students make [18]. Research has learned about the effects of instructional designs that can be useful for MOOCs' providers and students in their efforts to develop strategies to increase completion rates of MOOCs [19], as well as to determine the duration and analyze group behaviors [20] in order to implement different ways to increase the percentage of effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the good performance of deep learning, some researchers have used time series data as input data for deep learning to improve the accuracy of dropout prediction. For example, Wen et al [37] designed a two-dimensional matrix based on time series as an input to the CNN model, combining time information with the learner's behavioral features to solve the problem of local correlation of behavioral features using time series. Qiu et al [15] proposed an end-to-end dropout prediction model based on convolutional neural networks that integrates feature extraction and classification into a single framework.…”
Section: Time Series-based Study To Mooc Dropout Predictionmentioning
confidence: 99%
“…Guo et al (2019) chegaram a resultados que superam a precisão de soluções presentes no estado da arte em até 2,4%, e concluíram que sua pesquisa pode auxiliar professores e tutores a priorizar suas respostas e gerenciar melhor várias postagens, de modo que esses profissionais da educação possam responder às perguntas dos alunos em tempo hábil e ajudar a reduzir as taxas de evasão nesses cursos. Wen et al (2020) também utilizaram um modelo de AP para pesquisa no âmbito educacional, com o objetivo de identificar antecipadamente a desistência em Massive Open Online Courses (MOOCs). Nesse sentido, depois que Wen et al (2020) realizaram uma análise dos padrões de comportamento de aprendizagem dos alunos de um MOOC, relataram que esses estudantes geralmente exibem comportamentos de aprendizagem semelhantes em vários dias consecutivos (o status de aprendizagem de um aluno para o dia subsequente, provavelmente será semelhante ao do dia anterior).…”
Section: Arquitetura Multiplayer Perceptronunclassified
“…Wen et al (2020) também utilizaram um modelo de AP para pesquisa no âmbito educacional, com o objetivo de identificar antecipadamente a desistência em Massive Open Online Courses (MOOCs). Nesse sentido, depois que Wen et al (2020) realizaram uma análise dos padrões de comportamento de aprendizagem dos alunos de um MOOC, relataram que esses estudantes geralmente exibem comportamentos de aprendizagem semelhantes em vários dias consecutivos (o status de aprendizagem de um aluno para o dia subsequente, provavelmente será semelhante ao do dia anterior). Embasados nessa premissa Wen et al (2020) propuseram uma base de dados formada por atributos relacionados à correlação local de comportamentos de Souza, V. F., Santos, T. C. B. RBIE v.29 -2021 529 aprendizagem, sobre a qual aplicaram uma Rede Neural Convolucional, gerando um modelo para prever o abandono de alunos em MOOCs.…”
Section: Arquitetura Multiplayer Perceptronunclassified